Nursing Documentation Practices and Factors Impacting Patient Care: A systematic Review - Dafer Ali Dafer Albahri, Amal Hulayyil Alanazi , Bodoor Mohammed Alshehri , Haila Gazaa Alsubaie , Ghalbaa Eid Mousa Alamri Al Bishe , Enas Alamri (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Inadequate nursing documentation practices can detrimentally affect patient outcomes and the efficiency of healthcare professionals. While numerous individual studies have examined the prevalence of nurses' documentation practices , there lacks a consolidated prevalence estimate. Thus, this systematic review and meta-analysis aimed to evaluate the overall prevalenceof nursing care documentation practices and associated factors .Methods and Materials: This review exclusively considered published articles. Key databases searched included Medline/PubMed, Web of Science, Google Scholar, Scopus, the Cochrane Library. Cross-sectional studies meeting inclusion criteria and written in English were included.Utilizing a random effects model, the pooled prevalence of nurses' documentation practices was computed. Publication bias was assessed using funnel plots and the Egger's test. All statisticalanalyses were conducted using STATA version 14.